2016
DOI: 10.1007/s10548-016-0529-8
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Neural Adaptation and Predictive Coding Hypotheses in Auditory Change Detection

Abstract: The auditory mismatch negativity (MMN) component of event-related potentials (ERPs) has served as a neural index of auditory change detection. MMN is elicited by presentation of infrequent (deviant) sounds randomly interspersed among frequent (standard) sounds. Deviants elicit a larger negative deflection in the ERP waveform compared to the standard. There is considerable debate as to whether the neural mechanism of this change detection response is due to release from neural adaptation (neural adaptation hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…What are the likely cortical sources of the visual mismatch responses we observed in Experiment 2? The topographies of the frequency domain ( Figure 6C Figure 7B) appears to reflect a posterior negativity to surprising stimuli, accompanied by the negative dipole of a frontal positivity to surprising stimuli (for similar results see Dambacher et al, 2009;Symonds et al, 2017). The later part of the response (~330ms in Figure 7B) appears to instead be generated from bilateral posterior sources.…”
Section: Stimulus Repetition Inhibits Expectation Effectsmentioning
confidence: 55%
See 1 more Smart Citation
“…What are the likely cortical sources of the visual mismatch responses we observed in Experiment 2? The topographies of the frequency domain ( Figure 6C Figure 7B) appears to reflect a posterior negativity to surprising stimuli, accompanied by the negative dipole of a frontal positivity to surprising stimuli (for similar results see Dambacher et al, 2009;Symonds et al, 2017). The later part of the response (~330ms in Figure 7B) appears to instead be generated from bilateral posterior sources.…”
Section: Stimulus Repetition Inhibits Expectation Effectsmentioning
confidence: 55%
“…Recent work has found that repetition effects are larger for surprising stimuli, due to large surprise-related signal increases for unrepeated stimuli (Amado & Kovacs, 2016;Larsson & Smith, 2012;Choi et al, 2017;Kovacs et al, 2012Kovacs et al, , 2013reviewed in Kovacs & Vogels, 2014). Similar interaction effects have also been found for ERPs/ERFs, with several studies showing that expectation violation responses can be reduced when stimuli are repeated (Todorovic & de Lange, 2012;Symonds et al, 2017;Wacongne et al, 2011). Demonstrating similar interactions in visual oddball designs is critical to extending existing models of novelty/change detection (e.g., Kremlacek et al, 2016) to incorporate interacting mechanisms driven by recent stimulus exposure (stimulus repetition) and longer-term stimulus appearance probabilities (expectation).…”
Section: Introductionmentioning
confidence: 59%
“…Attention (broadly referring to the ability or power to concentrate mentally [Zenner et al, 2006;Fritz et al, 2007]) appears to serve the purpose of enhancing rather than generating predictive processes. Regularity formation and deviation detection can act independently of attention (Takegata et al, 2005;Winkler et al, 2005;Symonds et al, 2017). Chennu et al (2016) observed using electroencephalography (EEG) and magnetoencephalography (MEG) that attention modulates the strength and precision of prediction errors generated for omissions.…”
Section: Role Of Attention In Predictionmentioning
confidence: 99%
“…Similar surprise-related temporal components have been 94 reported in the studies of MEG (Magnetoencephalography) signals [34][35][36]. 95 An experiment specifically designed to account for the different brain reactions to 96 rare and frequent stimuli is the oddball task, in which a randomly composed 97 sequence of standard and deviant stimuli is presented to a subject [27,28,37]. 98 Previous surprise modeling studies mainly base their conclusions on a single 99 component extracted from the brain signals, with the MMN [27] or the P300 [12, 24, 100 25] or both [29] serving as the main such target components.…”
mentioning
confidence: 64%